Analisis Bahassa ditinjau dari Karakteristik, Isu Belajar dan Teori Bahasa - Yessa Maulida; Neviyarni Neviyarni (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2021)
This article discusses language in terms of children, issues and theories of language learning. Language is the special capacity that exists in humans to obtain and use complex communication systems, and a language is a specific example of such a system. Issues in language include language development, language and thought processes, language and animals, cultural differences in language and the relationship between the brain and language. Then the two theories of language learning approaches, namely the conditioning approach in language learning, have a basic assumption that language is studied in accordance with the principles of conditioning and a psycholinguistic approach.